Step
*
1
1
of Lemma
rv-circle-circle-lemma3'
.....assertion..... 
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. p : {p:ℝ^2| d(a;b) = d(a;p)} 
6. q : {q:ℝ^2| d(c;d) = d(c;q)} 
7. i : {x:ℝ^2| (d(c;p) = d(c;x)) ∧ (¬(c ≠ x ∧ x ≠ d ∧ (¬c-x-d)))} 
8. o : {y:ℝ^2| (d(a;q) = d(a;y)) ∧ (¬(a ≠ y ∧ y ≠ b ∧ (¬a-y-b)))} 
9. a ≠ c
10. d(c;p) = d(c;i)
11. ¬(c ≠ i ∧ i ≠ d ∧ (¬c-i-d))
12. d(a;q) = d(a;o)
13. ¬(a ≠ o ∧ o ≠ b ∧ (¬a-o-b))
14. ∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))
⊢ d(c;p) ≤ d(c;d)
BY
{ ((DoubleNegation THENA Auto) THEN (DistinguishCases ⌜c ≠ d⌝⋅ THENA Auto)) }
1
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. p : {p:ℝ^2| d(a;b) = d(a;p)} 
6. q : {q:ℝ^2| d(c;d) = d(c;q)} 
7. i : {x:ℝ^2| (d(c;p) = d(c;x)) ∧ (¬(c ≠ x ∧ x ≠ d ∧ (¬c-x-d)))} 
8. o : {y:ℝ^2| (d(a;q) = d(a;y)) ∧ (¬(a ≠ y ∧ y ≠ b ∧ (¬a-y-b)))} 
9. a ≠ c
10. d(c;p) = d(c;i)
11. ¬(c ≠ i ∧ i ≠ d ∧ (¬c-i-d))
12. d(a;q) = d(a;o)
13. ¬(a ≠ o ∧ o ≠ b ∧ (¬a-o-b))
14. ∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))
15. c ≠ d
⊢ ¬¬(d(c;p) ≤ d(c;d))
2
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. p : {p:ℝ^2| d(a;b) = d(a;p)} 
6. q : {q:ℝ^2| d(c;d) = d(c;q)} 
7. i : {x:ℝ^2| (d(c;p) = d(c;x)) ∧ (¬(c ≠ x ∧ x ≠ d ∧ (¬c-x-d)))} 
8. o : {y:ℝ^2| (d(a;q) = d(a;y)) ∧ (¬(a ≠ y ∧ y ≠ b ∧ (¬a-y-b)))} 
9. a ≠ c
10. d(c;p) = d(c;i)
11. ¬(c ≠ i ∧ i ≠ d ∧ (¬c-i-d))
12. d(a;q) = d(a;o)
13. ¬(a ≠ o ∧ o ≠ b ∧ (¬a-o-b))
14. ∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))
15. ¬c ≠ d
⊢ ¬¬(d(c;p) ≤ d(c;d))
Latex:
Latex:
.....assertion..... 
1.  a  :  \mBbbR{}\^{}2
2.  b  :  \mBbbR{}\^{}2
3.  c  :  \mBbbR{}\^{}2
4.  d  :  \mBbbR{}\^{}2
5.  p  :  \{p:\mBbbR{}\^{}2|  d(a;b)  =  d(a;p)\} 
6.  q  :  \{q:\mBbbR{}\^{}2|  d(c;d)  =  d(c;q)\} 
7.  i  :  \{x:\mBbbR{}\^{}2|  (d(c;p)  =  d(c;x))  \mwedge{}  (\mneg{}(c  \mneq{}  x  \mwedge{}  x  \mneq{}  d  \mwedge{}  (\mneg{}c-x-d)))\} 
8.  o  :  \{y:\mBbbR{}\^{}2|  (d(a;q)  =  d(a;y))  \mwedge{}  (\mneg{}(a  \mneq{}  y  \mwedge{}  y  \mneq{}  b  \mwedge{}  (\mneg{}a-y-b)))\} 
9.  a  \mneq{}  c
10.  d(c;p)  =  d(c;i)
11.  \mneg{}(c  \mneq{}  i  \mwedge{}  i  \mneq{}  d  \mwedge{}  (\mneg{}c-i-d))
12.  d(a;q)  =  d(a;o)
13.  \mneg{}(a  \mneq{}  o  \mwedge{}  o  \mneq{}  b  \mwedge{}  (\mneg{}a-o-b))
14.  \mforall{}x,y,z:\mBbbR{}\^{}2.    (d(x;y)  =  d(x;z)  \mLeftarrow{}{}\mRightarrow{}  ||z  -  x||  =  d(x;y))
\mvdash{}  d(c;p)  \mleq{}  d(c;d)
By
Latex:
((DoubleNegation  THENA  Auto)  THEN  (DistinguishCases  \mkleeneopen{}c  \mneq{}  d\mkleeneclose{}\mcdot{}  THENA  Auto))
Home
Index